Dysbiosis and metabolic pathway shifts in the gut microbiome of children with sepsis: a comparative analysis - Xu, Jiayue; Li, Jiru; Kong, Xiangmei; Zhang, Chen; Qi, Baocui; Zhu, Xiaodong; Zhu, Yueniu; Xu, Yaya (Frontiers in Microbiology, 2026)
BackgroundThe newly published Phoenix Sepsis Score in 2024 for assessing sepsis in children mainly focuses on respiratory, cardiological, coagulation and neurological indicators, whereas the gut microbiome also plays key roles in the occurrence and progression of sepsis. Additionally, emerging evidence suggests that specific biomarkers in gut microbiome are associated with disease progression. This study aimed to explore the differences in gut microbiome diversity, composition and function between septic and healthy children, and to establish correlations with clinical indicators and outcomes, providing new possibilities for the diagnosis and treatment of sepsis.ResultsAnalysis of gut microbiome was performed in 20 sepsis children and 9 healthy controls aged between 3 and 18 years old. The anal swab samples were analyzed by metagenomic next-generation sequencing. Significant differences were observed in α and β diversity of gut microbiome between sepsis group and healthy controls groups. Especially, Shannon diversity was significantly correlated with white blood cell count, serum lactate, length of pediatric intensive care unit stay and length of hospital stay (all R > 0, p < 0.05). Firmicutes and Bacteroidetes were both dominant in most of children in SG and HC groups, while three in SG showed extremely low combined abundances of Firmicutes and Bacteroidetes (<10%), which might be associated with chemistry therapy and death outcome. Bacteria associated with nosocomial infections, including genus taxa Acinetobacter, Prevotella, Escherichia, Klebsiella, Bacteroides, and Corynebacterium, can be dominant (relative abundance>70%) in sepsis group, which were absent in healthy control group. Enterococcus abundance not only predicted sepsis risk (AUC = 0.85) but also was correlated with 28-day mortality (R > 0, p = 0.004). Gene function prediction based on Kyoto Encyclopedia of Genes and Genomes pathway analysis indicated significant differences profile in SG and sepsis-deaths groups. The enriched gut microbiome genes were related to cellular proliferation, energy metabolism, signal transduction, the oxidative stress response and arginine metabolism.ConclusionSignificant differences in diversity, taxa composition and gene function in the gut microbiome existed between septic and healthy children. The associations between gut microbiome dysbiosis and clinical indicators were identified. Enterococcus could be a biomarker to predict sepsis risk.